Hemodynamics of Cerebral Aneurysm Initiation: The Role of Wall Shear Stress and Spatial Wall Shear Stress Gradient - Kulcsár, Z.; Ugron, Á.; Marosfői, M.; Berentei, Z.; Paál, G.; Szikora, I. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Cerebral aneurysms are preferentially located at arterial curvatures and bifurcations that are exposed to major hemodynamic forces, increasingly implicated in the life cycle of aneurysms. By observing the natural history of aneurysm formation from its preaneurysm state, we aimed to examine the hemodynamic microenvironment related to aneurysm initiation at certain arterial segments later developing an aneurysm. MATERIALS AND METHODS: The 3 patients included in the study underwent cerebral angiography with 3D reconstruction before a true aneurysm developed. The arterial geometries obtained from the 3D-DSA models were used for flow simulation by using finite-volume modeling. The WSS and SWSSG at the site of the future aneurysm and the flow characteristics of the developed aneurysms were analyzed. RESULTS: The analyzed regions of interest demonstrated significantly increased WSS, accompanied by an increased positive SWSSG in the adjacent proximal region. The WSS reached values of >5 times the temporal average values of the parent vessel, whereas the SWSSG approximated or exceeded peaks of 40 Pa/mm in all 3 cases. All patients developed an aneurysm within 2 years, 1 of which ruptured. CONCLUSIONS: The results of this hemodynamic study, in accordance with the clinical follow-up, suggest that the combination of high WSS and high positive SWSSG focused on a small segment of the arterial wall may have a role in the initiation process of aneurysm formation. AcomAanterior communicating arteryAFIaneurysm formation indicatorCFDcomputational fluid dynamicsDSAdigital subtraction angiographyGONgradient oscillatory numberICAinternal carotid arteryMRAMR angiographyPcomAposterior communicating arterySWSSGspatial wall shear stress gradientWSSwall shear stressWSSgwall shear stress gradient